2019
DOI: 10.1002/cncr.32060
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a role for stem cell transplantation in multiple myeloma?

Abstract: High‐dose chemotherapy and autologous stem cell transplantation (ASCT) are a standard of care for transplant‐eligible patients with newly diagnosed multiple myeloma (MM). The introduction of novel agents, which range from immunomodulatory drugs and proteasome inhibitors to monoclonal antibodies and have now been integrated into both induction and salvage regimens, has dramatically revolutionized the treatment landscape of MM and challenged the role of high‐dose chemotherapy and ASCT in treating MM. These advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…High-dose melphalan plus ASCT is a standard intensification strategy for the treatment of newly diagnosed (ND)MM patients younger than 70-75 years of age [63]. The role of ASCT has been frequently challenged in the past, but all studies reported a PFS advantage for patients receiving ASCT, as compared to no ASCT, although with an inconsistent OS benefit [62,[64][65][66].…”
Section: Incorporation Of Mrd Results Into Clinical Practicementioning
confidence: 99%
“…High-dose melphalan plus ASCT is a standard intensification strategy for the treatment of newly diagnosed (ND)MM patients younger than 70-75 years of age [63]. The role of ASCT has been frequently challenged in the past, but all studies reported a PFS advantage for patients receiving ASCT, as compared to no ASCT, although with an inconsistent OS benefit [62,[64][65][66].…”
Section: Incorporation Of Mrd Results Into Clinical Practicementioning
confidence: 99%
“…The role of tandem ASCT as an upfront treatment in cases with MM and its advantage over single ASCT are a matter of debate [11,12]. The development of extramedullary plasmacytomas during proteasome inhibitor treatment is also associated with an unfavorable prognosis in MM [13], and tandem ASCT could be considered in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a second autologous transplant can be performed if the patient received a significant benefit from the first transplant, commonly considered as a minimum of 18–24 months of remission. 32 In this way, many patients control their disease with sequential lines of treatment for many years; 47% of people diagnosed with MM in England and Wales survive their disease for 5 years or more and 33% survive their disease for 10 years or more. 1…”
Section: Treatment At Relapsementioning
confidence: 99%